Community-led application of Bacillus thuringiensis var. israelensis (Bti) effectively reduces malaria vector densities in The Gambia - BABUCARR JASSEY; RIRIH YUDHASTUTI; OMAR JALLOW; IBRAHIM TOURAY; MUHAMMAD RASYID RIDHA; KHULIYAH CANDRANING DIYANAH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Jassey B, Yudhastuti R, Jallow O, Touray I, Ridha MR, Diyanah KC. 2025. Community-led application of Bacillus thuringiensis var. israelensis (Bti) effectively reduces malaria vector densities in The Gambia. Biodiversitas 26: 3803-3814. Malaria remains a major public health burden in The Gambia, with Anopheles Meigen, 1818 mosquitoes thriving in seasonal patterns during peak transmission periods. Traditional vector control methods, such as insecticide-treated nets and indoor residual spraying, have shown limitations due to insecticide resistance and residual transmission. This study evaluates the impact of a community-led biolarviciding intervention using Bacillus thuringiensis var. israelensis de Barjac, 1978 (Bti) as an environmentally friendly and sustainable malaria vector control strategy. A field-based study was conducted across selected mosquito breeding sites in The Gambia, where trained community members applied Bti to target Anopheles larvae. Entomological surveys were carried out biweekly to assess larval and pupal densities, while adult mosquito populations were monitored in nearby households using CDC light traps. The study compared treated and untreated control areas to determine the intervention’s effectiveness. The application of Bti resulted in a significant reduction in Anopheles larval and pupal populations in treated areas compared to controls. Pupal emergence was nearly eliminated after consecutive rounds of Bti application, leading to a decline in adult mosquito densities. Community engagement contributed to the successful implementation and acceptance of the intervention, demonstrating the feasibility of integrating biolarviciding within existing malaria control efforts. Seasonal Bti application shows strong potential as a sustainable and complementary strategy to reduce mosquito breeding to ~90%, particularly when supported by enhanced community participation and operational resources to maximize long-term impact on malaria transmission.